2021
DOI: 10.1016/j.heliyon.2021.e07578
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy in physical activity and glycemic control among older adults with diabetes in Jagir Subdistrict, Surabaya, Indonesia

Abstract: Diabetes in older adults has shown an increase in prevalence, especially in urban areas of Indonesia. This study aimed to assess the relationship between self-efficacy in physical activity and glycemic control in older adults' population with diabetes mellitus in Indonesia. This research used cross sectional design that involved 52 adults with diabetes, aged between 55-90 years old who regularly attended the older adult's health post (Posyandu Lansia) at Jagir Sub-district, Surabaya. Those who had physical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…We show that most patients had abnormal HbA1C levels, indicating that glycemic control is still low among DM patients. Another study also reported poor glycemic control in Indonesia regarding glycated albumin as a marker of glycemic control in patients with type 2 diabetes (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…We show that most patients had abnormal HbA1C levels, indicating that glycemic control is still low among DM patients. Another study also reported poor glycemic control in Indonesia regarding glycated albumin as a marker of glycemic control in patients with type 2 diabetes (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing self-efficacy in patients with diabetes fatigue is significant. With good self-efficacy, patients can improve their ability to manage diabetes well [37,38]. In addition, self-efficacy can be the basis for patients to accept their illness so that the acceptance process can positively impact the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, self-efficacy also plays an important role in sports activities. Self-efficacy is a theoretical approach used to measure a person's belief in their capabilities to successfully execute a necessary course of action based on situational conditions (Mahmudiono et al, 2021).…”
Section: Methodsmentioning
confidence: 99%